The Immunoreactivity of recombinant protein MPT63 Mycobacterium tuberculosis as serodiagnostic tuberculosis - Fidhatami, Ian Imanuel; R Agus; M N Massi (Nusantara Medical Science Journal, 2024)
Introduction: Mycobacterium tuberculosis protein-63 (MPT63) is an extracellular protein encoded by the Rv1926c gene with a size of 16 kDa. MPT63 can specifically induce macrophage activation, stimulate cytokine production (TNF-α and IL-6), and stimulate Th1 cells. The immunogenic properties of MPT63 can be concluded from the presence of a high density of T cell epitopes in the N-terminal immunodominant. This research aims to emphasize and determine the antibody response from the administration of the MPT63 antigen as a candidate in active TB serodiagnostic testing. Methods:  This type of research is quantitative and is a diagnostic study. Serum samples were taken from Hasanuddin University Hospital stored biological material with 10 for healthy serum and 36 for sick serum. The determination of optical density values ​​is based on the results of the ELISA reader.  The determination of optical density values ​​is based on the results of the ELISA reader. Sensitivity and specificity were tested using the Mc Nemar formula and then they calculated the sensitivity and specificity values ​​manually. Results:  Based on the interpretation of the ELISA test from the MPT63 antigen, the antibody reaction response was obtained for a sensitivity of 50% and a specificity of 58.33%. Conclusions: Antibody responses to an antigen that is used indicate that all samples successfully respond well to the serum antigen in the serum of healthy and active tuberculosis but have a sensitivity that is still lacking.